Upaya Meningkatkan Prestasi Belajar Menulis Teks Pidato Melalui Metode Kolaborasi - Widodo, Suramto Tri (Lembaga Rumah Indonesia, 2021)
This study aims to improve the learning achievement of writing speech texts in Class VI Semester II SDN Kratonan No. 3 Surakarta Academic Year 2019/2020, which corresponds to Indonesian language learning on theme 7: Leadership; Sub Theme 1: Leaders Around Me on KI. 4.3